Pengaruh Servant Leadership, Dukungan Tim, dan Kepercayaan Organisasi terhadap Kreativitas Guru di Sekolah Dasar XYZ Daan Mogot - Eloise (Jurnal Ketopong Pendidikan, 2023)
Creativity is an important element that is highly needed in work for the progress and success of an organization. In the field of education, creativity is essential for teachers. Creativity is influenced by several extrinsic factors, including servant leadership, team support, and organizational trust. The purpose of this study is to examine the influence of servant leadership, team support, and organizational trust on teachers’ creativity. The research design employed is path analysis using a quantitative approach. The respondents consist of fifty two teachers, including all homeroom teachers and subject teachers at XYZ Elementary School, Daan Mogot, Jakarta. This study was conducted to determine whether servant leadership, team support, and organizational trust influence teachers’ creativity at XYZ School, with organizational trust serving as a mediating variable. In addition, the study also investigates whether servant leadership and team support influence organizational trust in XYZ School. The results indicate that servant leadership, team support, and organizational trust have a positive influence on teachers’ creativity.